1997
DOI: 10.1007/bf02766147
|View full text |Cite
|
Sign up to set email alerts
|

Improved motile sperm recovery by a hyperosmotic percoll gradient

Abstract: ~TRODUCTIONThe ideal semen processing technique should result in the selective recovery of good-quality motile sperm while maintaining a high total yield of recovered sperm. Several procedures for retrieving motile sperm from the ejaculate have been described, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Sperm incubation in media with high osmolarity lead to a progressive reduction of sperm total motility percentages and kinetic characteristics so that when sperm were suspended in medium with an osmolarity close to 600 mOsm residual sperm total motility was as high as 4.4%. The importance of medium osmolarity in the regulation of sperm motility has also been demonstrated previously during human sperm isolation using hyperosmolar Percoll preparations (Carbone et al, 1997). Finally, the demonstration that sperm motility characteristics improve when washed from seminal plasma with high osmolarity and resuspended in medium with lower osmolarity further strengthens the role of osmolarity in sperm motility regulation.…”
Section: Discussionsupporting
confidence: 70%
“…Sperm incubation in media with high osmolarity lead to a progressive reduction of sperm total motility percentages and kinetic characteristics so that when sperm were suspended in medium with an osmolarity close to 600 mOsm residual sperm total motility was as high as 4.4%. The importance of medium osmolarity in the regulation of sperm motility has also been demonstrated previously during human sperm isolation using hyperosmolar Percoll preparations (Carbone et al, 1997). Finally, the demonstration that sperm motility characteristics improve when washed from seminal plasma with high osmolarity and resuspended in medium with lower osmolarity further strengthens the role of osmolarity in sperm motility regulation.…”
Section: Discussionsupporting
confidence: 70%
“…Two discontinuous gradients with low centrifugal force applied were used clinically. Carbone et al [14] reported that use of a hyperosmotic gradient increased the yield of motile sperm, and Makler et al [8] reported that prolonging the centrifugation time to 60 min resulted in more nonmotile sperm being added to motile sperm. Under these conditions no attempt was made to reach a static endpoint.…”
Section: Discussionmentioning
confidence: 99%